2022
DOI: 10.1186/s12865-022-00496-2
|View full text |Cite
|
Sign up to set email alerts
|

High resolution HLA-DRB1 analysis and shared molecular amino acid signature of DRβ1 molecules in Occult hepatitis B infection

Abstract: Aim To investigate the association of human leukocyte antigen (HLA)-DRB1 alleles and the variations of polymorphic amino acid changes in DRβ1 chain in Shaanxi Han population with Occult hepatitis B infection (OBI). Methods High-resolution HLA-DRB1 genotyping was performed in 107 OBI carriers and 280 normal controls. Sequence information was used to assign which amino acids were encoded at all polymorphic positions. Three-dimensional modeling was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Another allele with potential protective roles against hepatitis B infection in Romanians is HLA-DRB1*15:01:01, a finding consistent with research done on other populations. A recent study on the Chinese population by Wang et al indicated that HLA-DRB1*15:01 was more prevalent in the control group than in occult hepatitis B virus infection carriers [26]. Similarly, studies on the same population by Yang et al identified HLA-DRB1*15 as the only allele linked to viral clearance [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another allele with potential protective roles against hepatitis B infection in Romanians is HLA-DRB1*15:01:01, a finding consistent with research done on other populations. A recent study on the Chinese population by Wang et al indicated that HLA-DRB1*15:01 was more prevalent in the control group than in occult hepatitis B virus infection carriers [26]. Similarly, studies on the same population by Yang et al identified HLA-DRB1*15 as the only allele linked to viral clearance [27].…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid variations in class II HLA have been documented as significant factors in various infectious diseases, including CHB [48]. Several reports show that HLA-DRB1 leucine at position 26 displays a positive association with the HBV vaccine response, while arginine at position 4, aspartic acid at position 57, and tyrosine at position 60 and position 78 exhibit a strong protective effect against occult hepatitis B infection [26,49]. To the best of our knowledge, this is the first report on amino-acid residues in HLA class II and CHB in the Romanian population.…”
Section: Discussionmentioning
confidence: 99%